THE INFLUENCE OF SPECIFIC BEHAVIOURAL BIASES ON RISK PERCEPTION AND INVESTMENT CHOICES (Lex localis - Journal of Local Self-Government, 2025)
The study investigates the ways in which particular behavioural biases affect how risk is perceived and investment decisions are made. It seeks to comprehend why investors frequently fail to meet their financial objectives and how to mitigate these psychological impacts. The availability heuristic, anchoring, loss aversion, and overconfidence biases are the main topics of the study. In contrast to traditional finance, behavioural finance recognises the psychological influence on investor behaviour. The study examined how different biases, such as herding, mental accounting, loss aversion, anchoring, availability bias, representativeness bias, and overconfidence, affect investment decisions using a mixed-methods approach. It also looked at the relationship between investor satisfaction and previous investment performance. Results indicate that individual investors' risk tolerance is greatly influenced by demographic variables such as age, education, and occupation. Investors frequently overemphasise historical performance and trend analysis. Decisions are also influenced by the availability of information, which results in a preference for domestic stocks. New investment decisions are often anchored by prior market experiences. Investors are confident in their choices, but they have differing opinions about beating the market. Many people have loss aversion, which makes them reluctant to increase their investments when stocks do poorly. The overall effect of herding behaviour on investment choices is negligible. Fewer investors think they are outperforming the market average, but the majority are happy with recent stock returns and overall investment decisions from the prior year. Gaining insight into these psychological factors is essential to enhancing investment performance and encouraging sound financial behaviour.